PENERAPAN METODE DRILL UNTUK MENINGKATKAN KEMAMPUAN HAFALAN DO'A SETELAH SHALAT DHUHA PADA SISWA KELAS IV MIN 20 ACEH BESAR - Ats-tsauri, Farhan; Marzuki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the drill method in teaching the memorization of the prayer recited after Dhuha prayer and to analyze the improvement of students' memorization ability in grade IV of MIN 20 Aceh Besar. This study used a Classroom Action Research (CAR) approach following the Kemmis and McTaggart model, carried out in two cycles with 32 students as research subjects. Data were collected through observation of teacher and student activities and an oral memorization test, then analyzed quantitatively and qualitatively. The results showed that the drill method was implemented through stages of prayer recitation by the teacher, classical imitation, group practice, pair practice, and individual practice in the form of memorization recitation, accompanied by direct correction of makhraj and tajwid errors. Teacher activity increased from 83.33% (good category) in Cycle I to 94.16% (very good category) in Cycle II, while student activity increased from 78.33% (good) to 90.83% (very good). The average memorization score increased from 71.44 to 79.41, with classical mastery increasing from 68.75% to 93.75%, exceeding the research success indicator of 75%. Thus, it can be concluded that the implementation of the drill method is effective in improving students' ability to memorize the prayer recited after Dhuha prayer in grade IV of MIN 20 Aceh Besar.